1990
DOI: 10.1210/jcem-70-1-173
|View full text |Cite
|
Sign up to set email alerts
|

The 25-KiloDalton Insulin-Like Growth Factor (IGF)-Binding Protein Inhibits both Basal and IGF-I-Mediated Growth of Chick Embryo Pelvic Cartilagein Vitro

Abstract: Insulin-like growth factor (IGF)-I stimulates the growth of many tissues, including growth plate cartilage. However, the role of IGF-binding proteins in the growth process is controversial. We purified a 25-kDa IGF-binding protein (BP-25) from amniotic fluid. We tested the effect of this BP-25 preparation on both basal and IGF-I-stimulated growth of chick embryo pelvic cartilages maintained in serum-free organ culture. Cartilage wet weight was 4.1 +/- 0.3 mg/cartilage initially; after 3 days, BP-25 inhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(60 citation statements)
references
References 31 publications
2
58
0
Order By: Relevance
“…In the circulation of normal, non-pregnant individuals, IGFBP-1 is present as a highly phosphorylated form. Other studies have used either recombinant IGFBP-1 which is non-phosphorylated (Cox et al 1994, Lee et al 1996 or IGFBP-1 purified from amniotic fluid which is deficient in the highly phosphorylated form (Frauman et al 1989, Burch et al 1990, Angervo et al 1991, Liu et al 1991, Lewitt et al 1993. We therefore purified phosphorylated IGFBP-1 from HepG2-conditioned medium and found it was more potent than npIGFBP-1 since it completely reversed the effects of IGF-I at a 1:1 molar ratio, while at this molar ratio npIGFBP-1 did not significantly inhibit IGF mitogenic actions.…”
Section: Discussionmentioning
confidence: 99%
“…In the circulation of normal, non-pregnant individuals, IGFBP-1 is present as a highly phosphorylated form. Other studies have used either recombinant IGFBP-1 which is non-phosphorylated (Cox et al 1994, Lee et al 1996 or IGFBP-1 purified from amniotic fluid which is deficient in the highly phosphorylated form (Frauman et al 1989, Burch et al 1990, Angervo et al 1991, Liu et al 1991, Lewitt et al 1993. We therefore purified phosphorylated IGFBP-1 from HepG2-conditioned medium and found it was more potent than npIGFBP-1 since it completely reversed the effects of IGF-I at a 1:1 molar ratio, while at this molar ratio npIGFBP-1 did not significantly inhibit IGF mitogenic actions.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis and secretion of IGFBPs are thought to play important roles in the regulation of IGF hormonal action at the target cell level at a time when the extracellular concentration of IGF-I remains constant (33)(34)(35). Depending on the circumstances, IGFBPs can either inhibit (35) or stimulate (34) the action of IGF-I on mammalian cells, but their predominant Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the circumstances, IGFBPs can either inhibit (35) or stimulate (34) the action of IGF-I on mammalian cells, but their predominant Figure 7. Effect of Ang II on the inhibitory effect of IGFBP-3 in hCG-induced PG production in perfused rabbit ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…These relationships suggest that cortisol might influence fetal growth through modulation of fetal IGFBP-1 concentrations. It has been shown that plasma levels of IGFBP-1 correlate with IGF-inhibitory activity in diabetic serum (Taylor et al 1990) and IGFBP-1 inhibits the growth of chick embryo cartilage in vitro (Burch et al 1990). IGFBP-1 concentrations are also related to cortisol concentrations in newborns (Cianfarani et al 1998) and children (Martinelli et al 1999).…”
Section: Hormonesmentioning
confidence: 99%